Diversity and Zonation of Benthic Amphipod Crustaceans Affected by the Mississippi Submarine Canyon in the Northern Gulf of Mexico - Yousria S. Soliman; Gilbert T. Rowe; Mary Wicksten; Chih-Lin Wei (Frontiers in Marine Science, 2022)
Amphipod crustacean diversity and zonation are described from the large Mississippi Canyon that extends from the continental shelf across the entire continental margin. Benthic amphipods were sampled on four cruises from 2000 to 2004 from six locations in the Mississippi Canyon from depths of 480 through 2,750 m, and compared with five locations in a second transect on the open continental slope approximately 100 km west of the canyon to assess the canyon effect on the structure and composition of amphipod assemblages. Five replicates were collected from each location using 0.2 m –2 GOMEX box corer. Amphipods amounted to 40% of the total faunal abundance within the canyon compared to only 4% in the non-canyon samples. Of the seventy-two species (19 families) collected, 61 were encountered in the canyon compared to 38 on the non-canyon transect. The trough-like head of the canyon (480 m) supported high densities (4,446–26,933 ind./m 2 ) of the filter feeding, tube dwelling ampeliscid amphipod ( Ampelisca mississippiana ), the highest densities sampled compared to any other single species, at any other location, either within or outside the canyon, reflecting extreme flux of organic detritus from the continental shelf. The dominance by this single species suppressed the within – habitat (alpha) diversity and evenness, compared to relatively high diversity within the 1,000–1,500 m depths interval both in and outside the canyon. The species richness and alpha diversity exhibited mid-depth maxima at ca. 1,100 m both in and out of the canyon. High species richness (61) over the entire length of the canyon is presumed to be a function of greater topographic complexity and intermittent mass wasting of sediment down the canyon axis. The absence of nestedness is attributed to the amphipod reproductive pattern that lacks dispersive larval stages and brooding comparatively small numbers of eggs in this taxon. Despite depressed diversity at the head of the canyon, the fact that the number of amphipod species in the Mississippi Canyon was 1.5 times their numbers on the adjacent slope suggests that this physiographic feature enriches geographic-scale species diversity.

Nestedness and species replacement along bathymetric gradients in the deep sea reflect productivity: a test with polychaete assemblages in the oligotrophic north‐west Gulf of Mexico - Carol T. Stuart; Solange Brault; Gilbert T. Rowe; Chih‐Lin Wei; Martine Wagstaff; Craig R. McClain; Michael A. Rex (Journal of Biogeography, 2017)
Aim To test the hypothesis that low productivity drives the nestedness component of β‐diversity in polychaetes at the deep‐sea floor. Location Western Gulf of Mexico. Methods We used A. Baselga's (2010, Global Ecology and Biogeography, 19 , 134–143) metrics of species replacement and nestedness to assess their overall significance with differences in depth and particulate organic carbon ( POC ) flux to the seafloor. We used M. A. Rodríguez‐Gironés & L. Santamaría's (2006, Journal of Biogeography , 33 , 924–935) BINMATNEST to calculate the significance and direction of nestedness with depth and POC flux. Results Nestedness was the most significant part of β‐diversity with depth and POC flux. The rank order of nestedness increased significantly with increasing depth, and decreased significantly with increasing POC flux. There was little endemism below 2000 m. Main conclusion The polychaete fauna in the deepest western Gulf of Mexico is largely a nested subset of the shallower upper to mid‐bathyal fauna. While the causes of β‐diversity in the deep sea are undoubtedly multivariate, the relative importance of turnover and nestedness appears to be modulated by productivity in the form of POC flux to the seafloor. Under circumstances of extremely low POC flux and animal density in the deepest reaches of the Gulf, nestedness may be caused by some populations being maintained by immigration from larger populations upslope, or by biogeographic filtering for tolerance to abyssal conditions. Resources at great depths in regions of exceptionally low productivity may be too limited to permit adaptation resulting in endemism and continued downslope turnover. If productivity helps to explain the nestedness part of β‐diversity, this may lead to a more unified theory of deep‐sea biodiversity.

Macrobenthos in the central Arabian Gulf: a reflection of climate extremes and variability - Chih-Lin Wei; Gilbert T. Rowe; Mohsin Al-Ansi; Ibrahim Al-Maslamani; Yousria Soliman; Nehad Nour El-Din; Ibrahim S. Al-Ansari; Ismail Al-Shaikh; Antonietta Quigg; Clifton Nunnally; Mohamed A. Abdel-Moati (Hydrobiologia, 2016)

Undetected Blooms in Prince William Sound: Using Multiple Techniques to Elucidate the Base of the Summer Food Web - Allison S. McInnes; Clifton C. Nunnally; Gilbert T. Rowe; Randall W. Davis; Antonietta Quigg (Estuaries and Coasts, 2015)

An alternative view of the role of heterotrophic microbes in the cycling of organic matter in deep-sea sediments - Gilbert T. Rowe; Jody W. Deming (Marine Biology Research, 2011)

Chemical Contaminants and their Effects in Fish and Wildlife from the Industrial Zone of Sumgayit, Republic of Azerbaijan - Carol D. Swartz; K.C. Donnelly; Arif Islamzadeh; Gilbert T. Rowe; William J. Rogers; Grigoriy M. Palatnikov; Arif A. Mekhtiev; Rafik Kasimov; Thomas J. McDonald; Jeffery K. Wickliffe; Bobby J. Presley; John W. Bickham (Ecotoxicology, 2003)

Editorial: The Unknown Environmental Tragedy in Sumgayit, Azerbaijan - John W. Bickham; Cole W. Matson; Arif Islamzadeh; Gilbert T. Rowe; K.C. Donnelly; Carol D. Swartz; William J. Rogers; Jeffrey K. Wickliffe; Robin L. Autenrieth; Thomas J. McDonald; Dmitri Politov; Grigoriy Palatnikov; et al. (Ecotoxicology, 2003)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)